How prepared are families for patients undergoing continuous ambulatory peritoneal dialysis therapy? - Fatimah, Siti; Khoiriyati, Azizah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
Family readiness is crucial in Continuous Ambulatory Peritoneal Dialysis (CAPD) therapy, as families play a central role as caregivers, helping to maintain care quality and reduce complications. This scoping review aims to systematically assess the literature to identify key aspects of family readiness in supporting patients undergoing CAPD therapy, highlighting its importance for better patient outcomes and its contribution to broader knowledge in patient care. Literature was selected using the Population and Concept (PC) framework, with the population of interest being families of CAPD patients and the concept focused on family readiness. Studies from 2015 to December 2023 were sourced from PubMed, Science Direct, PROQUEST, and Google Scholar, with inclusion criteria focusing on family involvement in CAPD care and exclusion criteria eliminating non-relevant studies. Ten articles met the criteria, revealing critical aspects of family readiness, including caregiving burden, communication with healthcare providers, knowledge of the disease and therapy, material and emotional support, and understanding of the dialysis service system. These factors are essential for ensuring quality care, reducing risks, and improving overall CAPD therapy success.